A new modified subgradient extragradient method for solving variational inequalities. Issue 1 (2nd January 2021) - Migórski, Stanisław; Fang, Changjie; Zeng, Shengda
Abstract : The goal of the note is to introduce a new modified subgradient extragradient algorithm for solving variational inequalities in Hilbert spaces. A result on the strong convergence of the algorithm is proved without the knowledge of Lipschitz constant of the operator. Several numerical experiments for the proposed algorithm are presented.